Peter Eisenman: Case X Caso - Mancini, Francesco (Quodlibet, 2017)
"Peter Eisenman: Case X Caso", is a critical essay reflecting on the contemporary crisis of habitation based on the early work of Peter Eisenman. The American author's early projects of six small houses are investigated in light of the structuralist and postmodernist thought, comparing Eisenman's theoretical position with his original design documents and sketches.